Climatic Projections of Lightning in Southeastern Brazil Using CMIP5 Models in RCP’s Scenarios 4.5 and 8.5 - Paes dos Santos, Ana Paula (2017)
Given the high and increasing lightning incidence over the Southeast of Braziland the various impacts that this phenomenon generates to society, there is agrowing need in predicting its occurrence, in order to minimize its consequences.In this context, this work presents the development of a methodologyfor the projection of lightning in the State of São Paulo (Southeastern Brazil),using the HadGEM2-ES and CSIRO-Mk3.6 models in two IPCC climatechange scenarios: RCP4.5 and RCP8.5. Since lightning is not an output variableof climate models, tests were carried out to evaluate the relationship betweenthe observed data of oceanic and atmospheric fields, which are knownas outputs of the models, and the lightning from the RINDAT and BrasilDATdetection networks. As result, a correlation of 0.84 was obtained. In the projections,it was verified that, while during a large portion of the current climatewe observed events of lightning below the average, the future climatereveals the preponderance of anomalously above average events, both in thescenario of intermediate-low emissions (RCP4.5) and in the scenario of highemissions (RCP8.5), suggesting a change in the pattern of the lightning incidencein the State of São Paulo.